An Overview of Type 2 Diabetes Mellitus (T2DM): Dental Implant Survival Rates - Mefina Kuntjoro; Nike Hendrijantini; Agus Dahlan; Husniya Juwita Farha; Mayang Aziza Hanif Ardianto (Indonesia Prosthodontic Association, 2022)
Background: Dental implants are an alternative treatment to replace missing teeth, as it is one of the oral health problems in the elderly. The success of dental implants is affected by a process known as osseointegration. Systemic conditions such as T2DM can interfere with the osseointegration process which can lead to implant failure. As the patient's blood glucose level increases, it will increase the accumulation of AGEs. These AGEs will interfere with the stages of bone-implant contact and also bone growth around the implant Objectives: To review dental implant survival rates in T2DM patients based on HbA1c, ISQ and CBCT examinations. Conclusion: Dental implants in T2DM patients after being evaluated for 2 years showed a good result. This result is obtained with the condition that HbA1c control is below 8%. Another solution to support the success of dental implants placement in T2DM patients is the use of delayed insertion technique and modification of the implant surface with HA or SLA is also recommended. Evaluation of implant success can also be done with pre-operative planning, such as evaluation of the bone condition with ISQ and CBCT examinations.